2015
DOI: 10.1111/acer.12883
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanol is Superior to Carbohydrate‐Deficient Transferrin and γ‐Glutamyltransferase as an Alcohol Marker and is a Reliable Estimate of Alcohol Consumption Level

Abstract: PEth was the biomarker with the best correlation to self-reported alcohol consumption. PEth was superior to CDT owing to its substantially higher sensitivity but also due to its closer correlation to self-report. PEth values can be translated into an approximate level of alcohol consumption and PEth appears to be a more reliable measure of alcohol consumption than self-reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 50 publications
(65 reference statements)
7
79
0
7
Order By: Relevance
“…The highest sensitivity of up to 99% was observed for Peth 31, 41 that showed a rapid decrease at the beginning of withdrawal, a slow decline after the first few days, and persistence at low levels beyond 19d of abstinence 42. Apart from biomarkers detected in blood and urine samples, saliva is a promising and easy accessible material to detect glycomarkers of oxidative stress,43, 44 but the reproducibility and validity in Peth has to be proven for clinical routine application 45. As an antibody based flash test is available for detection of EtG in urine with good sensitivity and specificity, this parameter is the most promising one to be integrated in routine laboratory settings and in screening of patients at risk to develop AWS 46…”
Section: Biomarkersmentioning
confidence: 99%
“…The highest sensitivity of up to 99% was observed for Peth 31, 41 that showed a rapid decrease at the beginning of withdrawal, a slow decline after the first few days, and persistence at low levels beyond 19d of abstinence 42. Apart from biomarkers detected in blood and urine samples, saliva is a promising and easy accessible material to detect glycomarkers of oxidative stress,43, 44 but the reproducibility and validity in Peth has to be proven for clinical routine application 45. As an antibody based flash test is available for detection of EtG in urine with good sensitivity and specificity, this parameter is the most promising one to be integrated in routine laboratory settings and in screening of patients at risk to develop AWS 46…”
Section: Biomarkersmentioning
confidence: 99%
“…There is a correlation between PEth and alcohol consumption level, PEth likely reflecting the exposition to alcohol over time, i.e., average blood alcohol concentration during several weeks before sampling [13,14]. However, in addition to the Fig.…”
Section: Discussionmentioning
confidence: 97%
“…PEth is an alcohol marker with high sensitivity in groups with excessive alcohol consumption (96-100%) [13,14,25]. The clinical sensitivity has been more varied in groups with low or moderate alcohol consumption, largely due to differences in sensitivity between analytical methods [14,16,26,27]. Hence, it has been reported that PEth can be used as a marker for low or moderate alcohol consumption using a method with improved analytical sensitivity [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should, however, be noted that recent clinical trials in alcohol-dependent individuals were unable to find a beneficial effect of varenicline based on self-reported alcohol consumption [212,213]. Nevertheless, when also monitoring the selective alcohol biomarker phosphatidylethanol (PEth) in the blood of the subjects in the above-mentioned clinical trial [212], it was found that varenicline indeed had effect on this objective measure of alcohol consumption [214] strengthening the potential of varenicline as potential novel medication for alcohol dependence. Besides glycine receptors and nAChR, there are various signalling systems indirectly targeting the mesolimbic dopamine system with promising preclinical findings on alcohol-mediated behaviours.…”
Section: Clinical Evidence For the Use Of Indirect Modulation Of Dopamentioning
confidence: 99%